The Effect of Debt-To-Equity Ratio and Return on Equity on Firm Value - Lama Bawa, Ulfa Ulwiyanti; Pamungkas, Leo Dadyo; Endarwati, Endarwati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to investigate the relationship between the market prices of publicly traded manufacturing businesses on the Indonesia Stock Exchange (IDX) between 2018 and 2022 and the Return on Equity (ROE) and Debt to Equity Ratio (DER). This study employs a quantitative technique to analyze secondary data from the annual financial statements of 111 companies chosen through intentional sampling. PBV acts as a stand-in for company value, and Der and ROE are used to assess capital structure and profitability, respectively. SPSS version 27 software was used to conduct a number of data analysis procedures, such as multiple linear regression, t-tests, F-tests, and traditional assumption tests. The findings demonstrate that, both separately and in combination, A company's value is positively and significantly impacted by ROE and DER. This suggests that by focusing on its capital structure and profitability, a company can raise its value to shareholders.